Turkish image in history books taught at french secondary schools - BİLEYDİ KOÇ, MALİKE (My University, 2023)
The past and the future are among the subjects that the human beings are most curious and wonder about. While the science of history provides a bridge to individuals and hence to the societies. Inter-communal grouping, which has become evident with the history of humanity, has become more acute in parallel to nation-state process. The individual has identified the nation he/she belongs to, with the concept of \"we\", whereas those outside his/her nation, with the concept of \"others\" and likewise science of history assuming a major function in nation building generated a field contributing to this perception. Therefore, historic facts could not possibly be considered at all times under an object viewpoint but were rather at times caused to serve a perception built-up one-sided, nurturing conflict culture. Education of history is of essence as well in respect of conceiving differences between societies from varying cultures besides bearing common memory in transferring the accumulation of every society to the next generations. Textbooks, which are one of the important tools of education, are read not only by a group but also by the students of a nation. It has a wide impact as it covers all segments of socity. This study aims to analyze how Turkish images are expressed in French Secondary School History Books with the method of imagology. In the textbooks, information is given about the Turks during the Hagia Sophia, the Byzantine Period, the Crusades, the Kanuni Period and the First World War. In this context, the way in which Turkish images used inhistory books are transferred to French students and the perceptions created within the framework of these images constitute the main subject of this study. As construal of the past has a direct influence on education, legislation, government policies and eventually the public perception, this study is of particular essence in respect of signifying how history education that secondary school students in France got acquainted with at an early age shape the image of the \"other\".
Fransız ortaokul tarih ders kitaplarında Türk imajı
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; TARİH; Arts & Humanities (AHCI); ARTS & HUMANITIES; HISTORY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; French History Education; Historiography; History Books of French Secondary Schools; Turkish History; Turkish İmage